Effect Of Electroless Plating On Wear And Surface Friction Of Alsi Cylinder Liner By Mukridz Bin Md Mohtar - Mohtar, Mukridz Md (2012)

(untitled)
A piston - liner wear simulator with a stroke length of 15mm is developed which can carry out testing at maximum speed of 500 rpm with temperature of 300°C. Aluminium-silicon (AlSi) alloy specimens are prepared from cast the AlSi alloy (ADC12) and cut to shape representing the circular profile of a 36mm diameter cylinder. The specimen is coated using electroless process with Ni-P-Cg-SiC composite coating of 35μm nominal thickness. The study covers the wear and friction measurement at 300 rpm and 200°C using the mineral oil SAE 40 and semi-synthetic oil SAE 5W-30. Wear measurement is evaluated progressively for 100 hours of the wear test using Alicona Infinite Focus G4 Microscope where the wear- depth, rate and volume together with the surface roughness are monitored. For the uncoated liners, the average roughness (Ra) decreases with time as the surface became smoother because of the surface peaks being removed during the experiment before it reaches a steady state. This trend is comparable to what have been obtained by previous researchers. The trends of the wear volume and wear depth for the uncoated liners are also very similar. The higher wear rate in the beginning before reaching steady state is comparable to the previous studies. Meanwhile, for the coated liner, the superior wear resistance of the Ni-P-Cg-SiC composite coating on the AlSi-alloy liner withstand only up to 40 hours of the wear test. Subsequently, a subsurface fatigue phenomenon is observed after 60 hours of the test which resulted in the exfoliation of some part of the coating film. In general, the highest wear loss is at dead centres compared to the middle stroke with the maximum wear depth for the coated liner is 14.4μm, followed by 6.4μm for the uncoated liner with SAE 40 lubrication and 6.3μm for the uncoated liner with SAE 5W-30 lubrication, respectively. For the piston ring which is harder than the uncoated AlSi-alloy liner, the wear depth is minimal. However, severe wear loss with a total wear depth of 315μm is observed for the piston ring of the coated liner due to rougher and harder Ni-P-Cg-SiC composite coating film. Measurement of the friction force shows that the differences between friction coefficient (μ) values at each location of the coated and uncoated liner specimens with different lubricant types are very small with the highest μ values is at dead centres which ranges between 0.18 to 0.19, while ranges between 0.10 to 0.11 at middle strokes. Unfortunately, the effect of the graphite particles as friction reducer for the coated liner is not observed in this study. In fact, the uncoated liner produces a lower μ value.